The Effects Of Science-Technology-Innovation On Competitiveness And Economic Growth - (:unkn) unknown (ELSEVIER SCIENCE BV, 2011)
Under the highly globalized and competitive world economy conditions, science-technology and innovation oriented competitiveness strategy is the most important factor for countries not only to strengthen their global competitiveness but also to achieve sustainable long run growth. Main aim of this study is to investigate the effects of science-technology-innovation oriented global competitiveness strategies and transmission mechanism on the economic growth for the high-income OECD. It is found that countries which have science-technology-innovation oriented global competitiveness strategies have sustainable competitiveness and long run growth. For this reason, countries should be designed science-technology-innovation oriented economic strategies and policies in order to achieve sustainable global competitiveness and long run growth.
Keywords: Competitiveness; Economic Growth; Technology-Innovation